The complete chloroplast genome of the lipstick tree, Bixa Orellana (Bixaceae). Issue 1 (2nd January 2019) - Dai, Seping; Li, Xuwen; Ni, Jianzhong; Ruan, Lin; Zhou, Renchao; Ng, Wei Lun
Abstract: Bixa orellana is a small tree known for its red, oil-soluble pigment contained in the seed coat that is used as a natural dye and food coloring. In this study, we assembled and characterized the complete chloroplast genome of B. orellana as a resource for future genetic studies. With a total length of 159, 825 bp, the chloroplast genome comprised of a large single-copy (LSC) region of 89, 476 bp, a small single-copy (SSC) region of 19, 617 bp, and two inverted repeat (IR) regions of 25, 356 bp each. A total of 127 genes were predicted, consisting of 83 protein-coding genes, 36 tRNA genes, and 8 rRNA genes. Phylogenetic analysis confirmed the position of B. orellana within the order Malvales.